An Analysis of Slang Language in Song's Lyric "The Man Who Can't Be Moved" by the Script - Hirim Rosinta Pane; Marlin Steffi Marpaung (Journal of Languages and Language Teaching, 2022)
Language is a bridge for people to communicate with one another in society. There is formal and informal language in the environment. This study focuses on slang language. Slang language is an informal way to communicate that is commonly utilized by adolescents. They may use slang, but some ages do not. As a result, slang language is only comprehended by certain people. As a result, slang is commonly used in songs. there are many songs that use slang language in the lyrics to deliver the song's purpose to the listener. This study uses descriptive qualitative methods to collect data from the lyrics of The Script's song "The Man Who Can't Be Moved." From the twelve types of slang that exist, five are included in the lyrics: clipping, compounding, coinage, mixing, and dialogue. According to the data, the most commonly used slang language in The Scripts song is blending, which has twelve blending terms inside the lyrics.